Integrative taxonomy reveals the first record and a new species for the previously monotypic genus Tethytimea (Tethyida: Tethyidae) in the Gulf of Mexico - Cruz-Barraza, José Antonio; Vega, Cristina; Ávila, Enrique; Vázquez-Maldonado, Laura Elena (Zootaxa, 2017)
The first record of the previous monotypic genus Tethytimea and the description of a new species from cryptic habitats of Gulf of Mexico are presented. Tethytimea carmelita sp. nov., is a red orange cushion shaped sponge (about 5 mm thick) with a tuberculate to granular surface. The spicular complement is formed by tylostyles (200–1120 µm length), smooth spheres (12.5–55 µm in diameter); megasters-spheroxyasters (12.5–90 µm in diameter); and micrasters in two categories: oxy-strongylasters (12.5–27.5 µm in diameter) and spherotylasters (2.5–25 µm in diameter). The new species differs from the only species known T. tylota (Hentschel, 1912) mainly by differences in the size and shape of spicules. T. tylota possesses tylostyles in two size categories; megasters include giant oxyspherasters up 250 µm and micrasters in a single category. Additionally, to the morphological characteristics, we integrated partial sequences of a large sub-unit ribosomal 28S rDNA gene region (D1–D2 domains), in order to establish the molecular taxonomic position of our new species (and genus). Tree topologies (Maximum Likelihood and Bayesian Inference) were congruent in phylogenetic hypothesis, retrieving the Order Tethyida as monophyletic. In this clade, the family Timeidae was separated from the other families Tethyidae + Hemiastrellidae. Inside this latter group and according to the taxonomic hypothesis based on morphology, Tethytimea carmelita sp. nov. was included in Tethyidae clade, together with a sequence of Tethya sp. (AY626300), forming a sister group with representatives of genera Xenospongia and Thectitethya. Our new species constitutes the second valid known species for the genus Tethytimea and the first record of genus for the Atlantic Ocean.